HMGA2 cooperates with either p27kip1 deficiency or Cdk4R24C mutation in pituitary tumorigenesis. Issue 5 (4th March 2018) - Fedele, Monica; Paciello, Orlando; De Biase, Davide; Monaco, Mario; Chiappetta, Gennaro; Vitiello, Michela; Barbieri, Antonio; Rea, Domenica; Luciano, Antonio; Papparella, Serenella; Arra, Claudio; Fusco, Alfredo
ABSTRACT: We have previously reported a critical role of HMGA proteins in pituitary tumorigenesis since either the Hmga1 or Hmga2 gene overexpression/activation induces the development of mixed growth hormone/prolactin cell pituitary adenomas by activating the E2F transcription factor 1, and then enhancing the G1/S transition of the cell cycle. Consistently, amplification and overexpression of the HMGA2 gene was found in human pituitary prolactinomas. Since impairment of the cell cycle control represents a feature of experimental and human pituitary adenomas, we have investigated the possible synergism between the alterations of other cell cycle regulators, such as p27 deficiency or Cdk4 R24C mutation, with Hmga2 overexpression in pituitary tumorigenesis. Therefore, we crossed the Hmga2/T mice, overexpressing the truncated/active form of the Hmga2 gene, either with the knockout mice for p27 kip1, or with the knockin mice for the Cdk4 R24C mutation, both developing pituitary adenomas. Increased incidence and decreased latency in the development of pituitary lesions appeared in double mutant Hmga2/T;Cdk4 R24C mice, and increased features of invasiveness and atypia were observed in pituitary tumors of both Hmga2/T;p27-ko and Hmga2/T;Cdk4 R24C double mutant mice as compared with single mutant compounds. Interestingly, most of these mice develop pituitary adenomas with high Ki67 index, extrasellar expansion and brain tissue infiltration, representing good mouse models for human aggressive pituitary adenomas. Taken together, the results reported here indicate a cooperation between HMGA2 overexpression and either p27 kip1 or CDK4 impairment in promoting pituitary tumor development and progression.